2017
DOI: 10.1021/acschemneuro.7b00080
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminus Binding Preference for Either Tanshinone or Analogue in Both Inhibition of Amyloid Aggregation and Disaggregation of Preformed Amyloid Fibrils—Toward Introducing a Kind of Novel Anti-Alzheimer Compounds

Abstract: Amyloid-β (Aβ/Aβ) peptide with a length of 40 or 42 residues is naturally secreted as cleavage product of the amyloid precursor protein, and formation of Aβ aggregates in a patient's brain is a hallmark of Alzheimer's disease (AD). Therefore, disaggregation and disruption provide potential therapeutic approaches to reduce, inhibit, and even reverse Aβ aggregation. The disaggregation/inhibition effect of the inhibitors applies generally to both Aβ and Aβ aggregations. Here we capture the atomic-level details of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 77 publications
2
26
0
Order By: Relevance
“…We hypothesize that these structural changes facilitate the breakage of the fibril and encourage the dissociation of monomers from fibril ends. The other probable outcome of these effects, particularly alteration in the twist angle between layers, is that the accommodation of monomers into the fibril end, through the “dock-lock” mechanism, becomes difficult since the twisted cross-β structure increases a steric energy barrier for incorporating additional monomers into the ends of seed fibrils. , Replica exchange simulations of fibrillization thermodynamics have shown that, in contrast to Aβ peptides buried in the fibril interior which have in-registry arrangements, those on the fibril edges are off-registry . These partially ordered surface subunits have been suggested by authors to serve as targets for anti-aggregation molecular agents and could readily be dissociated from fibril ends upon deviations in the twist angle between the stacked peptides.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We hypothesize that these structural changes facilitate the breakage of the fibril and encourage the dissociation of monomers from fibril ends. The other probable outcome of these effects, particularly alteration in the twist angle between layers, is that the accommodation of monomers into the fibril end, through the “dock-lock” mechanism, becomes difficult since the twisted cross-β structure increases a steric energy barrier for incorporating additional monomers into the ends of seed fibrils. , Replica exchange simulations of fibrillization thermodynamics have shown that, in contrast to Aβ peptides buried in the fibril interior which have in-registry arrangements, those on the fibril edges are off-registry . These partially ordered surface subunits have been suggested by authors to serve as targets for anti-aggregation molecular agents and could readily be dissociated from fibril ends upon deviations in the twist angle between the stacked peptides.…”
Section: Results and Discussionmentioning
confidence: 99%
“…6C6 prefers to recognize an epitope located in the NT of Aβ, and a slight inhibition effect was obtained after addition of other amyloid peptide antibodies, such as mAb 1C2, which binds to region His13‐Lys28 of Aβ and was considerably less effective for restoring the solubility of the peptide, and mAb 14C2, which raises against the C‐terminal region, had no sensitive effect on Aβ solubility, similar to the unrelated mAb CP4 . These results indicate that the NT plays a key role in the Aβ molecule for fibrillar genesis and therapeutic interest, but has been paid less attention so far. Experiments found that the NT can exhibit different conformations and solubility properties depending on environmental conditions, and at intermediate pH (4–7) an oligomeric Aβ 42 structure (the probable structure in plaques) predominates, and the β‐sheet structure observed at pH 4–7 is intermolecular .…”
Section: Resultsmentioning
confidence: 99%
“…Celltoxicity experiments reported on a significant level of tanshioneinduced protection of cultured SH-SY5Y cells, indicating that tanshinones are effective inhibitors of Aβ-induced in vitro toxicity. Alternative modes of interactions have been proposed, based on simulations employing different fibril models as starting states (Wang et al, 2013;Dong et al, 2017). Most recent MD simulations in explicit solvent, using a combination of secondary structural analysis, MM-PBSA binding energy calculations, and radial distribution functions computations, indicated that the charged residues within the disordered N-terminus tail of Aβ40 and Aβ42 are the preferred targets of tanshinones (Dong et al, 2017).…”
Section: Natural Compounds With Inhibitory Effects On Aβ Peptide Aggrmentioning
confidence: 99%
“…Alternative modes of interactions have been proposed, based on simulations employing different fibril models as starting states (Wang et al, 2013;Dong et al, 2017). Most recent MD simulations in explicit solvent, using a combination of secondary structural analysis, MM-PBSA binding energy calculations, and radial distribution functions computations, indicated that the charged residues within the disordered N-terminus tail of Aβ40 and Aβ42 are the preferred targets of tanshinones (Dong et al, 2017). According to the simulations, TS molecules favor a disaggregation mechanism driven by the interaction between TS and the N-terminal region of Aβ42 fibril, with a shift of the β1 region and a consequent fibril twist around its fibril axis.…”
Section: Natural Compounds With Inhibitory Effects On Aβ Peptide Aggrmentioning
confidence: 99%